A new formula for a mild body cleanser: sodium laureth sulphate supplemented with sodium laureth carboxylate and lauryl glucoside. (3rd April 2014) - Takagi, Y.; Shimizu, M.; Morokuma, Y.; Miyaki, M.; Kiba, A.; Matsuo, K.; Isoda, K.; Mizutani, H.
Synopsis Objective Sodium laureth sulphate (SLES) is an anionic detergent, which has been used globally for personal care products because of its mildness and good foaming ability. However, SLES is somewhat invasive and stimulatory to the skin, and many consumers with sensitive skin desire milder detergents for daily use skin cleansers. We enhanced the mildness of SLES by formulating it with sodium laureth carboxylate (AEC) and lauryl glucoside (LG). Methods In skin soak tests, 5% detergent solutions were applied to the forearms of 10 Japanese healthy volunteers for 30 min followed by washing with tap water once a day for 4 days. Twenty‐four hours after the last treatment, cutaneous capacitance measurements and visual analyses were performed. In a controlled usage study, 16 Japanese healthy volunteers used the test body cleanser for 4 weeks. Assessment of efficacy and mildness was conducted prior to the start of the study and at the end of week 4 by cutaneous conductance, dermoscopic evaluation of the stratum corneum and visual assessment by a dermatologist. Results In soak tests, cutaneous capacitance was significantly decreased on the soap‐treated region and on the SLES‐treated region. No significant decrease was identified on the SLES/AEC/LG‐treated region with less induction of erythema or dryness. In the controlled usage study, no significant changes in cutaneous conductance or texture or damage of corneocytes on the forearm and lower thigh were found. However, visual assessment revealed a significant decrease in scaling and erythema on the lower thigh after 4 weeks of usage with an improvement of the discomfort of the consumer. The favourability rating of this formulated detergent in several questionnaire items was very good. Conclusion The newly formulated skin cleanser with the combination of anionic surfactants SLES and AEC and the non‐ionic surfactant LG provides a mild surfactant with a satisfactory cleansing activity for body washing.